Naming myself - Stoneburner, Sarahbeth, author; Levy, EJ, advisor; Alexander, Ruth, committee member; Fletcher, Harrison, committee member (Colorado State University. Libraries, 2017)
Naming Myself is a collection of twelve nonfiction essays and short memoirs unified by a theme of identity: particularly what is means to name yourself, and name past experiences to claim authority in one's life. The elements of identity explored include the quest for individuality by means of finding a suitable name; finding an identity compromised of two faith traditions; naming sexual violence; mental health; memorializing my father, and naming as an act of awakening by claiming the title of "feminist."